BioDiv-Web: Integrating structured project-based learning with citizen science to enhance critical thinking and environmental literacy - Tsaniyah, Uswatul Wadhichatis; Muhdhar, Mimien Henie Irawati Al; Muntholib, Muntholib (JPBIO (Jurnal Pendidikan Biologi), 2025)
The escalating global biodiversity crisis underscores the critical need for effective educational strategies that promote environmental awareness and competencies. This research and development study addresses this imperative by designing and evaluating "BioDiv Web," an innovative e-learning platform for biodiversity education. The platform synergistically integrates the Structured Project-Based Learning (SPjBL) model with a Citizen Science Project (CSP) approach to create an authentic and scaffolded learning environment. Developed using the Lee and Owens model, the product was validated by experts and deemed highly valid (e.g., material validation: 100%) and practical (average score: 92%) based on trials with students. A quasi-experimental study involving 70 tenth-grade students was conducted to assess its effectiveness. The experimental group exhibited significantly higher learning gains compared to the control group. The results demonstrated moderate effectiveness, with normalized gain scores of 0.68 for critical thinking skills and 0.65 for environmental literacy. One-way ANCOVA analysis confirmed that these improvements were statistically significant (p < 0.001). The findings affirm that the BioDiv Web platform is a robust, practical, and effective digital tool for enhancing senior high school students' critical cognitive and affective learning outcomes in biodiversity education.